Справочник по цифровой схемотехнике - Зубчук Виктор Иванович (Тэхника, 1990)
Экземпляры: КХ (20081115) / Инвентарный номер: 980903 / Цена: / Сис.шифр: 32.844 / Авт.знак: З-91 / ГРНТИ: 47.33.31 / ББК: 32.844.15